PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI PADA SMK PGRI MAJA KABUPATEN LEBAK-BANTEN - Mita; Lestari, Dewi (Journal of Research and Publication Innovation, 2024)
This study aims to determine the influence of Work Discipline and Physical Work Environment on Employee Performance at SMK PGRI MAJA Lebak – Banten. The method used is quantitative with an associative approach. The population was 57 sampling techniques using saturated sampling and a sample of 57 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients, and hypothesis tests. The results of this study are that Work Discipline has a significant effect on employee performance with the regression equation Y = 16,883 + 0,574X1, the correlation value is 0,664, the determination coefficient value is 44,1% with the hypothesis test obtained t calculation > t table or (6,589 > 2,004). The Physical Work Environment had a significant effect on employee performance with the regression equation Y = 16,145 + 0,588X2, correlation value of 0,616, determination coefficient of 37,9% with hypothesis test obtained t calculation > t table or (5,795>2,004). Work discipline and physical work environment simultaneously have a significant effect on employee performance with the regression equation Y = 8,901 + 0,415X1 + 0,371X2, correlation value of 0,747, determination coefficient value of 55,8% while the remaining 44,2% is influenced by other factors. The hypothesis test obtained a value of F calculated > Ftable or (34,059 > 2,780).